The Odd couple - Koch, Howard W.; Saks, Gene ([Hollywood, Calif.] Paramount Pictures, 1967)
Neil Simon has a special genius for finding the great hilarity ordinary people doing everyday things. Like two divorced men who decide to share a New York apartment.
Jack Lemmon, Walter Matthau.
VHS format.
In English.
Keywords: Comedy films